Patterns of Antimicrobial Resistance in the Causative Organisms of Spontaneous Bacterial Peritonitis: A Single Centre, Six-Year Experience of 1981 Samples - Sara Sheikhbahaei; Alireza Abdollahi; Nima Hafezi-Nejad; Elham Zare (International Journal of Hepatology)
Background/Aims. Spontaneous bacterial peritonitis (SBP) is one of the leading causes of morbidity and mortality in patients with cirrhosis. This study aims to determine the microbial agents of SBP and the pattern of antibiotic resistance, in a large number of ascitic samples. Methodology. In a cross-sectional, single center, hospital based study, 1981 consecutive ascitic fluid samples were recruited from 2005 to 2011. Samples were dichotomized into three-year periods, in order to assess the trend of resistance to the first-line empirical antibiotics. Results. SBP was found in 482 (24.33%) of samples, of which 314 (65.15%) were culture positive. The most prevalent isolated pathogen was E. coli (33.8%), followed by staphylococcus aureus (8.9%) and Enterococcus (8.6%). No significant changes in the proportion of gram-negative/gram-positive infections occurred during this period. A percentage of resistant strains to cefotaxime (62.5%, 85.7%), ceftazidim (73%, 82.1%), ciprofloxacin (30, 59.8%), ofloxacin (36.8%, 50%), and oxacilin (35%, 51.6%) were significantly increased. E. coli was most sensitive to imipenem, piperacillin-tazobactam, amikacin, ceftizoxime, and gentamicin. Conclusions. The microbial aetiology of SBP remains relatively constant. However, the resistance rate especially to the first-line recommended antibiotics was significantly increased. This pattern must be watched closely and taken into account in empirical antibiotic treatment.